Kompetensi Arsiparis Dalam Pengelolaan Kearsipan Terhadap Pemenuhan Kebutuhan Informasi Masyarakat - Iwin Ardyawin (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2017)
The level of civilization of a nation can be seen from the maintenance and preservation of its archive. In this respect, archive need to be well managed in a proper system framework. Good archive is managed by archivist who can support the archievement of the process of archiving and improve service for the community in the delivery of information in the institusion or agency. The requires a qualified archive and competence in the field. The image of archive is strongly influenced by the archivists have a great responsibility in the process of filling and can increase the existence of institusion and agency.